Pareto Frontier Approach to Determining the Optimal Path on Multi-Objectives - Pratiwi, Annisa; Nasution, M.K.M.; Herawati, E. (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Every issue we face in daily life can be resolved through mathematical modeling. The use of mathematical modeling to generate solutions frequently produces value that serves a single purpose. Sometimes a single-purpose function's solution does not offer the best solution value. In this study, the author models the multiobjective time-dependent vehicle routing problem using the Ant Colony Optimization (ACO) metaheuristic algorithm. The author then applies the pareto optimization principle to the determination of the optimal starting point for the route. An optimal Pareto frontier principle solution on a multi-objective model under control of the Ant Colony Optimization algorithm is the outcome of this study.